The Determination of the Effect to Shelf Life of Marinated Crayfish (Astacus leptodactylus Esch., 1823) with Rosemary and Thyme Essential Oils Additive - Duman, Muhsine; Emir Coban, Ozlem; Ozpolat, Emine (Kafkas Univ, Veteriner Fakultesi Dergisi, 2012)
In this study, chemical [pH and thiobarbituric acid (TBA)], microbiological (Total aerobic bacteria, psychrophilic bacteria, lactic acid bacteria and yeast-mould count) and sensory analyses were performed to investigate the qualitative changes of crayfish marinated with rosemary and thyme essential oils during the storage at 4 degrees C. According to the results, statistically no significant difference was found in pH values amongst groups (P>0.05). However, the difference between control group and essential oils applied groups were significant (P<0.05) in term of TBA values. During the storage, the difference between control group and essential oils applied groups in term of the total aerobic bacteria, psychrophilic bacteria, lactic acid bacteria and yeast-mould counts were statistically found significant (P<0.05). The sensory evolution results indicated that the shelf life of marinated crayfish was 42 days for the control, 56 days for the rosemary and 70 days for the thyme essential oils applied groups. In conclusion, essential oils showed a positive effect on the product's shelf-life; particularly thyme essential oil is noteworthy in this regard. The use of oils mentioned was a positive impact on the chemical and microbiological quality of the products.
Biberiye ve Kekik Esansiyel Ya?ları Katkısının Marine Edilmiş Kerevitlerin (Astacus leptodactylus Esch., 1823) Raf Ömrüne Etkisinin Belirlenmesi
Keywords: Crayfish; Marinating; Rosemary essential oil; Thyme essential oil; Essential oils; Shelf-life